Mitochondrial dysfunction and kidney disease - Sultan Khalid Al Dalbhi; Fatimah Abdullah Alqarni; Nawaf Messad Bahatheq; Reem Saleh Alrasheed; Rufaydah Ali Alkhowaiter; Areej Abdulaziz Alnughaimshi (Society of Diabetic Nephropathy Prevention, 2019)
Context: Mitochondria play a vital role in producing the energy needed for different cellular activities. The role of mitochondria in different diseases and the aging process is gradually being clarified. Different studies have suggested that mitochondrial dysfunction due to mutations in genes that maintain the integrity of mitochondrial DNA (mtDNA), mitophagy, and apoptosis can lead to many neurological and muscular phenotypes as well as diseases in other organ systems including liver, gastrointestinal tract, heart, and kidneys. We examined the current knowledge of mitochondrial dysfunction and its role in renal pathophysiology. Additionally, we examined how chronic kidney diseases can lead to mitochondrial dysfunction through oxidative stress accumulation, which can subsequently lead to other pathological complications. Evidence Acquisitions: Directory of Open Access Journals (DOAJ), Google Scholar, PubMed (NLM), LISTA (EBSCO), and Web of Science have been searched. Results: The renal pathological manifestation of mitochondrial dysfunction includes tubular defects, focal segmental glomerular sclerosis (FSGS), glomerular dysfunction, interstitial nephritis, and cystic kidney disease or renal tumors. These conditions can be caused by mutations in the nuclear genes that are involved in mtDNA replication and transcription or due to mtDNA mutations in the genes involved in the respiratory chain. Conclusions: Clearly, mtDNA plays an important role in renal pathology, and mitochondria may serve as a potential therapeutic target to treat different renal pathologies.